Shelf life prediction and kinetics of quality changes in pineapple (Ananas comosus) varieties at different storage temperatures - Mohd Ali, Maimunah; Hashim, Norhashila; Abd Aziz, Samsuzana; Lasekan, Ola (Multidisciplinary Digital Publishing Institute, 2022)
Shelf life estimation is an important factor to predict the freshness of fruits. This study aimed to investigate the shelf life and the changes in the physicochemical properties of three different pineapple varieties, namely MD2, Josapine, and Morris stored at 5, 10, and 25 °C. The effect of storage temperature on pineapple changes in total soluble solids, pH, moisture content, firmness, and colour was evaluated for 21 days of the storage period. It was revealed that different storage temperatures have a significant effect on the shelf life and quality of different pineapple varieties. The firmness and moisture content showed high regression coefficients, hence were used for the shelf life prediction of pineapple based on kinetic models. By using first-order kinetics, the coefficient of determination (R2) values for quality changes in pineapples ranged from 0.893 to 0.992. The results also demonstrated that the samples stored at 10 °C had the longest shelf life in relation to the changes in firmness and moisture content of the fruit. The findings indicated that shelf life estimation plays an important role to improve the quality preservation of fresh fruits and vegetables during storage.